5.9 Behavioural, social and emotional outcomes following late and moderately preterm birth. (9th June 2014) - Johnson, S; Draper, ES; Evans, TA; Field, DJ; Guy, A; Marlow, N; Seaton, LS; Smith, ELK; Boyle, EM
Abstract : Introduction: Very preterm (<32 weeks) infants are at high risk for behaviour problems. Relatively little is known about behavioural outcomes following birth at late and moderately preterm gestations (LMPT; 32–36 weeks). Methods: 1130 LMPT and 1255 term-born (≥37 weeks) babies were recruited to the Late and Moderate Preterm Birth Study (LAMBS). At 2-years, parents completed the Brief Infant and Toddler Social Emotional Assessment (BITSEA) questionnaire to screen for socio-emotional and behaviour problems, and the Modified-Checklist for Autism in Toddlers (M-CHAT) questionnaire to screen for autistic features. Parents of children with positive M-CHAT screens completed a follow-up interview to improve specificity of screening over use of the questionnaire alone. Results: Parents of 651 (59%) LMPT and 771 (62%) term-born infants responded at 2-years. Overall, 38% of LMPT and 30% of term-born children had positive BITSEA screens (RR 1.23, 95%CI 1.06 to 1.42); however, LMPT children were at increased risk for delayed social-emotional competence (RR 1.42, 1.17 to 1.73) but not behaviour problems (RR 1.15, 0.93 to 1.42). LMPT children had significantly higher risk of positive M-CHAT screens (15% vs. 9%; 1.58, 1.18 to 2.11). After follow-up, LMPT children remained at significantly higher risk for autistic features (2.4% vs. 0.5%; 4.52, 1.51 to 13.56). Conclusions: LMPT children are at increased risk for social-emotional but not behaviour problems at 2 years of age. This is the first study to show an increased risk for autistic features in LMPT infants. Longer term follow-up is needed to determine how these behavioural sequelae evolve throughout childhood.